Byttehandel i Grønland - Exe Christoffersen, Erik (Peripeti, 2022)
Barter trade in Greenland This essay addresses the principles of Odin Teatret’s ‘barter trade’ used for a project in Greenland from 2021 to 2024. It is an artistic device which Odin Teatret has used since 1974. Barter trade breaks down traditional conventions of theatre usually taking place outside theater institutions and doesn’t make use of narrative dramaturgy. During the barter trade the performers “exchanges” their own material with the audience and facilitate a process of response between players and audience when performing songs, dances and/or scenes. The method can be described in terms of what the French philosopher Jacques Rancière calls The Ignorant Teacher (2007).